We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
387
2
avatar

How is e^x = sin(x) + cos(x) if sin(1)+cos(1) =/ e^1

 May 23, 2017
 #1
avatar
0

I don't exactly know what you are trying to derive !!?? But we have:

 

Cos(Pi) = -1 and Sin(pi) =0, hence:

Cos(pi) + i Sin(Pi) = -1, so that: e^(i*Pi) = -1

 May 23, 2017
 #2
avatar+7499 
0

There is a mistake...

Correct one : \(e^{ix}=\cos x + i\sin x\)

.
 May 25, 2017

9 Online Users

avatar